(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Screening and comparison of antimicrobial action of leaf extract of Aerva lanata and Momordica charantia. Ethyl acetate and methanolic extracts of leaves of plants were screened for antimicrobial activity using the cup plate method and the spread plate method against gram positive and gram negative reference organisms (Bacillus substilis and Escherichia coli).The standard antibacterial agent used for reference is Choramphenicol and the results were calculated as zone of inhibition. Methanolic extract showed comparatively broader and better antimicrobial spectrum than ethyl acetate extract in selected plants. Plant extracts showed dose dependent action, results were similar to the action of the standard Choramphenicol. Extracts of Aerva lanata and Momordica charantia demonstrated antimicrobial activity on tested microorganisms. Methanolic extracts showed higher antimicrobial potential than ethyl acetate extract. Aerva lanata extracts showed better response than Momordica charantia extracts in the cup plate method antibacterial activity with Bacillus substilis and Escherichia coli.